1999
DOI: 10.1144/0050293
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic development of the Norwegian margin 60–64°N: sequences and sedimentary response to variable basin physiography and tectonic setting

Abstract: The Cenozoic development of the Norwegian margin between 60 and 64°N can be described in terms of five, unconformity-bounded, megasequences: Paleocene–lowermost Eocene (65–51 Ma), Lower Eocene–lowermost Oligocene (51–31 Ma), Lower–upper Oligocene (31–24 Ma), Miocene–Pliocene (24–1.9 Ma), and Pleistocene (1.9 Ma–present). Each sequence is constructed of systems tracts, varying in type and number between sequences. In the Møre Basin (62–64°N), lowstand wedges dominate and form an offlapping, regressive pattern. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 21 publications
4
82
0
Order By: Relevance
“…Jordt et al 2000;Rasmussen 2004). The northern North Sea was subject to uplift, subaerial erosion, and associated valley incision into Oligocene strata during the Miocene (Jordt et al 2000 and references therein) and seismic mapping has led to proposed incised valleys draining NW into the Møre Basin (Martinsen et al 1999). Major eastward shelf progradation off NE Greenland has been proposed to be of Miocene age based on seismic interpretation (Hamann et al 2005), and must reflect a major uplift event of the NE Greenland margin regardless of the precise age.…”
mentioning
confidence: 99%
“…Jordt et al 2000;Rasmussen 2004). The northern North Sea was subject to uplift, subaerial erosion, and associated valley incision into Oligocene strata during the Miocene (Jordt et al 2000 and references therein) and seismic mapping has led to proposed incised valleys draining NW into the Møre Basin (Martinsen et al 1999). Major eastward shelf progradation off NE Greenland has been proposed to be of Miocene age based on seismic interpretation (Hamann et al 2005), and must reflect a major uplift event of the NE Greenland margin regardless of the precise age.…”
mentioning
confidence: 99%
“…After Cretaceous thermal subsidence, a new rifting event west of Shetland led to opening of the North Atlantic during earliest Eocene time (Eldholm et al 1987). Simultaneously, the Shetland Platform and the Norwegian mainland were uplifted and became source areas for Palaeocene and Eocene deep marine turbiditic sands entering the North Sea Basin (Martinsen et al 1999;Ahmadi et al 2003). Smectite clay, in upward increasing amounts in the Rogaland Group and totally dominating the lower Hordaland Group, is an erosion product from volcanic ash and rocks related to the rifting and opening (Thyberg et al 2000;Peltonen et al 2008;Marcussen et al 2009).…”
Section: Petroleum System and Geological Settingmentioning
confidence: 99%
“…There is no generally accepted geological model that explains the nature of the top Hordaland Group unconformity. Rundberg & Eidvin (2005) believed it was formed by submarine erosion whereas Martinsen et al (1999) suggested that the unconformity was formed during subaerial exposure and erosion of the northern North Sea. The top Hordaland Group unconformity is time equivalent to the mid-Miocene unconformity, which has been mapped regionally throughout the North Atlantic (Brekke 2000;Stoker et al 2005;Doré et al 2008).…”
mentioning
confidence: 99%
“…Some workers favour a Paleogene onset of uplift for southern Norway, but most available evidence strongly suggests a primarily Neogene event (Rundberg & Smalley 1989;Jensen & Schmidt 1993;Jordt et al 1995;Rohrman et al 1995;Riis 1996;Martinsen et al 1999). …”
Section: Mechanisms Proposedmentioning
confidence: 99%
“…Recently, some progress has been made with respect to timing, and two phases that have influenced the whole North Atlantic region have been identified (e.g. Riis 1996; Martinsen et al 1999). The first is a Paleogene phase primarily associated with Eocene rifting and contemporaneous volcanism generated by the Iceland mantle plume (e.g.…”
mentioning
confidence: 99%